Effects of trigonal deformation on electronic structure and thermoelectric properties of bismuth. (25th June 2018) - Wu, C Y; Han, J C; Sun, L; Gong, H R; Liang, C P
Abstract: First principles calculation and Boltzmann transport theory have been used to reveal the effects of trigonal deformation on electronic structure and thermoelectric properties of bulk bismuth. It is found that the semimetal-semiconductor transition would happen at the critical c / a points of 2.41 and 2.51, and that such a transition should be ascribed to the opposite changes of band edges at T and L points during trigonal deformation. Calculations also reveal that trigonal deformation has an important effect on various temperature-dependent thermoelectric properties, and that carrier density plays a decisive role in determining the magnitude of Seebeck coefficient and figure of merit. The semimetal  →  semiconductor transition as a result of trigonal compression with the decrease of c / a fundamentally induces the best performance of the thermoelectric properties of bismuth at the c / a ratio of 2.45. The present results agree well with experimental observations in the literature, and provide a deep understanding of the intrinsic relationship between trigonal deformation, band structure, and thermoelectric properties of bismuth.